2016
DOI: 10.3847/0004-637x/833/1/12
|View full text |Cite
|
Sign up to set email alerts
|

VLA AND ALMA IMAGING OF INTENSE GALAXY-WIDE STAR FORMATION IN z ∼ 2 GALAXIES

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
198
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(241 citation statements)
references
References 91 publications
43
198
0
Order By: Relevance
“…Rujopakarn et al (2016) confirmed this offset using the JVLA and 2MASS, measuring ∆δ = +0.26 ± 0.13 , and suggesting an issue in the absolute astrometry of the HST images. None of our targets falls in the HUDF, so we cannot directly double check their result.…”
Section: Note On the Astrometrymentioning
confidence: 69%
“…Rujopakarn et al (2016) confirmed this offset using the JVLA and 2MASS, measuring ∆δ = +0.26 ± 0.13 , and suggesting an issue in the absolute astrometry of the HST images. None of our targets falls in the HUDF, so we cannot directly double check their result.…”
Section: Note On the Astrometrymentioning
confidence: 69%
“…This difference could be due to a systematic difference in the absolute astrometric calibration between UKIDSS and ALMA. It is not possible to verify this, as there are no other sources in the field within the ALMA field-of-view beam, but similar offsets between ALMA and optical/near-infrared images have been reported (e.g., in the Hubble Ultra Deep Field; see Aravena et al 2016;Rujopakarn et al 2016). No offset from the UKIDSS position was seen in the PdBI data (Venemans et al 2012).…”
Section: Fir Continuummentioning
confidence: 80%
“…The Herschel systems studied in this paper can also be compared to the high-resolution studies of z∼4 star-forming galaxies by Wiklind et al (2014), Hodge et al (2016), and Rujopakarn et al (2016) with HST and radio/submillimeter imaging with the VLA and ALMA, which reveal similar trends, namely disturbed host galaxy morphologies and starforming regions offset from the centroid of the stellar light (XMMC2_30 is a very good example). The fact that these morphologies persist into the K band (rest-frame optical) in the sample studied in this paper suggest that the appearance of these objects is not dominated by clumpy extinction, but instead reflects the actual distribution of stellar light.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, by combining near-infrared imaging of the stellar light with high-resolution radio continuum imaging (which pinpoints the regions of star formation or nuclear activity in these systems) we can build up a much more complete picture of the nature of the galaxies. This is particularly valuable in dusty star-forming systems, where the peak of star formation activity may be offset from the peak of the visible stellar light (Rujopakarn et al 2016(Rujopakarn et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation